(untitled) (Journal of Medical & Health Sciences Review, 2025)
The present study critically studies the awareness and early detection of breast cancer in females of all ages. The analysis of the present research explores the real importance of awareness and early detection of breast cancer in females from different walks of life. Breast cancer is the leading cause of death in females and an emerging challenge for new-era technology. The awareness about breast cancer and early detection of the disease is constructive and a step to save humanity from fatal results. The data collected on breast cancer was derived from interviews with 50 women with breast cancer and the questionnaire was filled after signs and symptoms of breast cancer. Data has been collected from the oncology department NHM. The present result highlights the commonality of breast cancer in females is due to a lack of awareness and no facility for early detection of breast cancer. So, the findings demonstrate women experience breast cancer due to a lack of awareness as females are largely ignorant that could get cancer but are not allowed to visit their doctors. In turn, they have to put their lives into Death Valley. So, the commonality of diminished breast cancer can be reduced by the awareness programs among women about breast cancer.